Refleksi Pandangan Nietzsche terhadap Moralitas dan Kepentingan Diri - Indrajaya, Ferdinand (Humaniora, 2010)
This research is a reflection, a result from author’s contemplative process, in reading one of the texts written by one of the western philosopher at the end of modernity, Friedrich Nietzsche. The reading itself, mainly, was initially started from Nietzsche’s own writing in a form of excerpts collected in an anthology entitled Self-Interest. This research wishes to show how Nietzsche responds to existing understanding on traditional morality, which to him is no more than a kind of slave morality. Nietzsche, with his own view on morality is basically orbiting to one of his main theses, Will to Power (der Wille zur Macht); other morality related concerns like self and self-interest are also undetachable to this Will to Power. Within the context of traditional morality, thing like self-interest is considered taboo in contrast with altruistic behaviour (self-less behaviour by emphasizing concerns to others). For Nietzsche, this kind of morality is prevailed necessarily because we’re discourageous in facing the arrival of nihilism. From Nietzsche’s perspective, an immoralist, a person with self-interest (within the context of traditional morality) is a ‘moralist’ him/herself. The one who affirms to nihilism, the one who possesses master morality. At the end of this research, the author gives his own response regarding to his reading on Nietzsche and to aim pragmatic value from this research might be impossible. What might be possible is one can aim at achieving different perspectives on morality and self-interest through Nietzsche’s perspective.